Historical Retrospection and Trends in the Development of the National Accounting Standards in Bulgaria - Savova, Kameliya (Research Papers, 2022)
The article presents the origination, the development, the application and the perspectives of the National Accounting Standards in Bulgaria. The aim of the study is to present the evolution and the development trends of the National Accountants in Bulgaria. Based on empirical research, it is established that they are the preferred financial framework for reporting and their implementation has increased over the years. Data from the International Financial Reporting Standards Foundation prove that the application of accounting standards for non-public companies is a common practice in an international aspect and Bulgaria participates in this process. The research methodology is based on the general principles of knowledge, applying the systematic approach, the methods of analysis and synthesis, the empirical research and generalization, the comparative graphic analysis. A study of statistical data on the number of enterprises in Bulgaria that have adopted the National Accounting Standards as a framework for financial reporting, and the structure of the economy according to the categories of enterprises defined in the Accountancy Act was conducted. The content of the study is useful for the history and the theory of accountancy in Bulgaria, for the governmental authorities related to the accounting legislation, for the professional organizations involved in the evolution and improvement of the National Accounting Standards.